Perceived Organizational Support, Coworkers’ Conflict and Organizational Citizenship Behavior: The Mediation Role of Work-Family Conflict - Andrade, Cláudia (2022)
The aim of the present study is to investigate the extent to which perceived organizational support and coworkers’ conflict and work-family conflict play a role in the performance of three types of organizational citizenship behaviors. A cross-sectional design was used comprising a sample of 164 health support workers working in Portuguese elderly care facilities. Using structural equation model findings showed that perceived organizational support is linked with organizational citizenship behaviors, directly and indirectly, via work-family conflict. Furthermore, coworkers’ conflict was also related with organizational citizenship behaviors, directly and indirectly via work-family conflict. The linkage between perceived organizational support and coworkers’ conflict through work-family conflict can offer new insights into how to enhance organizational citizenship behaviors by active management. These findings can help elderly care organizations and their managers to design better workplace conditions where organizational support and coworkers’ conflict can be better managed allowing workers to have more control over work-family conflict and promoting organizational citizenship behaviors.